Dimerization of Intermediate P+–C–O– Dipolar Ions into Carbaphosphatrane Derivatives during Intramolecular Cyclization of 2-R-4,4-Bis(trifluoromethyl)benzo[f][1,3,2]dioxaphosphepin-5-ones - Mironov, V. F.; Ivkova, G. A.; Litvinov, I. A.; Islamov, D. R.; Khayarov, Kh. R. (Russian journal of organic chemistry, 2022)
2-R-4,4-Bis(trifluoromethyl)benzo[ f ][1,3,2]dioxaphosphepin-5-ones containing an endocyclic carbonyl group, when stored or slightly heated, undergo spontaneous intramolecular cyclization into P + –C–O – -bipolar ions containing benzoxaphosphole and oxaphosphethane rings fused along the P–C bond. These ions further dimerize into carbaphosphatrane derivatives with a pentacoordinate phosphorus atom, where the P–C bond is incorporated simultaneously into four-, five-, and six-membered rings. Hydrolysis of the carbaphosphtranes leads to the formation of benzo[ d ][1,2]oxaphosphole derivatives. The structure of one of the carbaphosphatranes, as well as one of the benzo[ d ][1,2]oxaphospholes has been proved by X-ray diffraction analysis. Carbon substituents in the carbaphosphatrane occupy apical positions, whereas the more electronegative oxygen atoms are in equatorial positions.